Murine allergic rhinitis and nasal T(h2) activation are mediated via TSLP- and IL-33-signaling pathways - Akasaki, Shoko (Int Immunol, 2016)
Thymic stromal lymphopoietin (TSLP) and IL-33 are epithelium-derived proallergic cytokines that contribute to allergic diseases. Although the involvement of TSLP in allergic rhinitis (AR) is suggested, the exact role of TSLP in AR is poorly understood. Furthermore, the relative contribution of TSLP and IL-33 in nasal allergic responses has not been described. In this study, we examined the roles of TSLP and IL-33 in AR by analyzing acute and chronic AR models. Acute AR mice were intraperitoneally immunized with ragweed, then intranasally challenged with ragweed pollen for four consecutive days. Chronic AR mice were nasally administrated ragweed pollen on consecutive days for 3 weeks. In both models, TSLP receptor (TSLPR)-deficient mice showed defective sneezing responses and reduced serum ragweed-specific IgE levels compared with wild-type (WT) mice. Analyses of bone-marrow chimeric mice demonstrated that hematopoietic cells were responsible for defective sneezing in TSLPR-deficient mice. In addition, FcεRI(+)-cell-specific TSLPR-deficient mice showed partial but significant reduction in sneezing responses. Of note, T(h2) activation and nasal eosinophilia were comparable between WT and TSLPR-deficient mice. ST2- and IL-33-deficient mice showed defective T(h2) activation and nasal eosinophilia to acute, but not chronic, ragweed exposure. TSLPR and ST2 double-deficient mice showed defective T(h2) activation and nasal eosinophilia even after chronic ragweed exposure. These results demonstrate that TSLPR signaling is critical for the early phase response of AR by controlling the IgE-mast-cell/basophil pathway. The IL-33/ST2 pathway is central to nasal T(h2) activation during acute allergen exposure, but both TSLPR and ST2 contribute to T(h2) responses in chronically allergen-exposed mice.